Legal and Ethical Challenges in Regulating the Use of Health Technology - Yusuf Brilliant; Yeni Jayanti; Ahmad Fikri (Research Horizon, 2026)
Advances in digital technology have driven transformation in healthcare systems through innovations such as telemedicine, artificial intelligence, and electronic medical records. While offering efficiency and accessibility, the use of these technologies raises complex legal challenges that are not yet fully accommodated in positive law, particularly in Indonesia. The purpose of this study is to analyze the legal issues of health technology use in Indonesia and provide recommendations for legal reform to ensure patients’ rights are protected ethically and fairly. This study uses a normative-conceptual approach to examine legal issues arising in the context of health technology, including personal data protection, liability for technological errors, the validity of informed consent, and jurisdictional conflicts in telemedicine. The results of the study indicate an urgent need to reform existing regulations, establish technology audit mechanisms, improve legal literacy among medical personnel, and strengthen cross-regional cooperation. Thus, legal reform is an important prerequisite for ensuring the ethical and fair use of health technology and protecting patients’ rights.